Management application of feeding with different fasting methods in milkfish seeding (Chanos chanos) - Ayuzar, Eva; Khalil, Munawwar; Wijaya, Heni (Acta Aquatica: Aquatic Sciences Journal, 2021)
Milkfish has a high market demand, the existence of consumption milkfish is influenced by the success of the nursery. This study aims to determine the effect of feeding different feeding methods on milkfish to milkfish. The research was carried out from September to October 2020 at the Hatchery and Aquaculture Technology Laboratory, Faculty of Agriculture, Malikussaleh University. The experimental research method used a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, namely A: Control (given daily feed), B: 1 day of fasting, 3 days of feeding, C: 2 days of fasting, 2 days of feeding feed, D: 3 days of fasting, 1 day of feed. The results showed that the feeding method of fasting was different with the best treatment found in treatment B, namely 1 day fasting, 3 days of feeding. Behavior, increased appetite, normal movement and normal metabolism, daily feed consumption of 1.23 grams, total feed consumption of 39.26 grams, length growth of 2.03 cm, weight growth of 3.06 grams, feed efficiency of 73.96%, Feed conversion was 1.35 and had a significant effect on survival, with treatment A having the highest survival, namely 87%.Keywords: Efficiency, Fasting, Feed, Growth, Milkfish